Hepatitis B Core-Related Antigen and New Therapies for Hepatitis B - Takehisa Watanabe; Takako Inoue; Yasuhito Tanaka (Microorganisms, 2021)
The hepatitis B core-related antigen (HBcrAg) is an unprecedented novel HBV biomarker that plays an essential role in reflecting covalently closed circular DNA (cccDNA) in chronic hepatitis B (CHB) because its levels correlate with intrahepatic cccDNA and serum HBV DNA. In this review, we describe the clinical application of serum HBcrAg in CHB patients, with a particular focus on new therapies targeting intrahepatic HBV replication. (1) HBcrAg can be detected in clinical cases where serum HBV DNA is undetectable during anti-HBV therapy. (2) A highly sensitive HBcrAg assay (iTACT-HBcrAg) may be useful for monitoring HBV reactivation, as an alternative to HBV DNA. (3) Decreased HBcrAg levels have been significantly associated with promising outcomes in CHB patients, reducing the risk of progression or recurrence of hepatocellular carcinoma. Additionally, we focus on and discuss several drugs in development that target HBV replication, and monitoring HBcrAg may be useful for determining the therapeutic efficacies of such novel drugs. In conclusion, HBcrAg, especially when measured by the recently developed iTACT-HBcrAg assay, may be the most appropriate surrogate marker, over other HBV biomarkers, to predict disease progression and treatment response in CHB patients.